Reading Material Based Gender and Cultural Familiarity and Its Implementation - Susanti, Elis (Universitas Muhammadiyah Jember, 2018)
The schemata theory in reading explains that in the process of comprehending a reading material, a pre-exsistent knowledge of the readers will be active when they read a piece of reading material in which it presents a familiar vocabulary, patterns, or contexts in which they fit into the readers’ pre-exsistent knowledge. As a result, readers can recognize what they read because it fits into patterns what they already known. This research was categorized as a type of research and development in which it developed a reading material on the basis of the readers’ interest and content familiarity which was constructed under the concept of schemata theory in reading. The research stages consisted of conducting praresearch, developing a prototype, validating the prototype, and applying the design to the research sample. The researchers took a class of X social science class in SMAN 1 Abung Semuli consisting of 32 students as the research sample to apply the prototype of this research development product. The data analysis shows that the use of reading material based gender and cultural familiarity gives significant influence on the students’ reading comprehension in which to the conclusion that the prototype of this research product is effective to be used as a reading material in a reading class.